The Modality of Mulyadi Jayabaya’s Political Clan in the Lebak Local Election in 2018 - Imron Wasi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research discusses a number of strengths or capital possessed by the Mulyadi Jayabaya political clan in the electoral process at the 2018 Lebak regional head election, as well as having brought up his daughter in the 2018 regional head elections as a representation of one of the local political clans that has dominated the political-economic structure. The incumbent’s success in this electoral process has cemented the status quo among political clans. In addition, this victory cannot be denied because of the symbolic power that has been obtained by the incumbent. As stated in the study of Pierre Bourdieu (1986), who has seen that in the social arena there are always those who dominate and are dominated. Thus, to analyze the amount of capital owned by the Mulyadi Jayabaya political clan, the author uses a concept that has been conveyed by Pierre Bourdieu regarding capital, which consists of economic capital, social capital, cultural capital, and symbolic capital. This research addresses a number of capitals that are used ath the same time in an effort to maintain their power in fighting the empty column and civil society members who are members of the fight group for empty column because capital has a significant role, especially the political legacy that has been abandoned by the previous regent. As a result, incumbents and political clans build networks formally, such as with the bureaucracy, and with informal leaders, such as religious leaders, youth, and organizations, in the aftermath of clan member’s victories in the 2018 Lebak regional head election.